Genomic insights into diversity, antimicrobial resistance and virulence of Glaesserella parasuis from diseased swine in Peru - Alvarez-Vega, Luis; De La Cruz-Monroy, Karolina S. M.; Garcia-Barraza, Arturo; Carhuaricra, Dennis; Llaja-Bernedo, Jose L.; Huamancha-Pulido, Liseth L.; Medina-Gonzales, Alejandra; Sedano-Sanchez, Andre F. (Frontiers in Microbiology, 2025)
Glaesserella parasuis is an important bacterial pathogen and the etiological agent of Glässer’s disease, which causes substantial economic losses on swine farms worldwide. Although large scale genome studies have been carried out in the North hemisphere, few genomes from South America are available limiting our knowledge of the full genetic diversity of this bacteria. In this study, seventeen clinical G. parasuis isolates from diseased swine in Peru where whole genome sequenced and compared with publicly available genomes. We identified seven distinct sequence types and five serotypes being more prevalent: the emergent ST454 and novel ST726 and serotypes 7 and 12. Although most isolates did not carried any antimicrobial resistance gene (ARG) we identified a large cassette of ∼50 kb carrying nine different ARGs (aac(3)-IV, aph(3′)-Ia, aph(3′)-Ib, sul2, blaROB–1tetB, lnuH, estT and floR) including six tandem repeats of estT and floR genes. We also identified two coexisting small plasmids harboring tetH, estT and blaROB–1 in two isolates. Most of the isolates (88.2%, 15/17) harbored at least one group 1 vtaA virulence gene. The G. parasuis diversity was segregated in two clades (C1 and C2) by phylogenetic and gene content analysis. We identified several genes overrepresented in both clades, however three metabolic operons (glnHMPQ, hisGDCBHAFI, thiDEM) were almost exclusive of C2 strains suggesting that C1 strains are auxotrophs for histidine and thiamine important nutrient for bacterial survival which may impact in the adaptation of these strains to the host niche. Our results suggest a high diversity of G. parasuis strains circulating in Peru, the presence of mobile elements carrying multiple ARGs underscores the need for continuous surveillance of this pathogen within the Peruvian swine industry to identify potential vaccine candidates and formulate better control programs.